Online Short-Circuit Protection Strategy of an Electric Powerpack for Electric Oil Pump Applications - Noh, Youngwoo; Kim, Wonkyu; Lee, Ju (IEEE access, 2021)
With the trend towards the miniaturisation and electrification of automotive components, the electric oil pump (EOP) is generally designed as an integrated powerpack in which a motor and an electronic control unit (ECU) are combined into an integrated system, with the electronic components of the ECU exposed to harsher temperature environments. The critical weakness of the traditional design is short-circuit failures, and the most common protection method is V_{ds} monitoring. However, this method cannot predict the accurate protection current, indicating that the fault detection level and short-circuit current (SCC) may change depending on the operating temperature and load condition to which the devices are subject. In this case, switching devices can be destroyed or deteriorated if they are unexpectedly placed outside of the protection range. This study proposes an online short-circuit protection method in which the optimal fault threshold can be controlled in real time, in accordance with changes in temperature and load conditions. To this end, this study investigates the cause of fluctuations in SCC and analyses the protection range and qualification time for SCC through worst-case analysis. To determine the optimal fault threshold, the SCC waveform is estimated through circuit analysis and a method of estimating R_{dson}(T_{j}) , which is the cause of SCC fluctuation, is proposed based on simulation and experimental data. Finally, according to R_{dson}(T_{j}) , optimal thresholds are derived and the proposed methods are experimentally-verified. It is found that the SCC could be predicted and managed within the protection range by the proposed new protection method.